Undtagelsesmodstand: Klimanød, undtagelsestilstand og aktivistisk temporalitet - Jacobsen, Stefan Gaarsmand (K&K - Kultur og Klasse, 2020)
This article examines various political criticisms of the State of Exception in light of climate activists’ desire to declare a climate emergency in a large number of states globally. These criticisms have developed in tandem with notions of securitization and de-politicization of the environment since the 1990s, and the article argues that several theorists overlook the temporal perspective of the climate crisis and risks of irreversibility in destroyed ecosystems. These risks – and their temporalities – should be included in the assessment of discursive issues surrounding the activists’ demands for a state of emergency. Since the criticisms revolve around questions of sovereignty, the article points to a more specific analysis of sovereignty futures, where climate risks are determinative, but where temporality still plays a minor role.